Data "Technology Exploration on Zero-Emission Regional Aircraft" - Pontika, Evangelia; Laskaridis, Panagiotis (Cranfield University, 2026)
The present datasets are the results of the exploration and comparison of zero-emission technology strategies for regional aircraft. A novel, holistic approach that captures inter-dependencies, synergies and combined impact of technologies is developed to evaluate the feasibility of such aircraft over 2 horizons, quantify performance and emissions through various phases of the life cycle, establish technology bottlenecks and required step changes and classify developments in terms of impact and risk. Three variants are considered: a fuel cell aircraft, a battery aircraft and a hybrid fuel cell / battery aircraft.
Keywords: Fuel Cells; Batteries; Hydrogen; Aviation; Roadmaps